FAKTOR-FAKTOR YANG MEMPENGARUHI KELEMAHAN PENGENDALIAN INTERNAL PADA PEMERINTAH DAERAH - Dwi Nurmala Sari (2022)
This study aims to prove the effect of the size of the local government, local generated revenue, capital expenditure, social assistance expenditure, and follow-up audit results on the problem of internal control weaknesses in local government institutions. The population used in this study is all district/city governments in Indonesia for the period 2019. Sampling in this study used purposive sampling. A sample of this research consisted of 382 local government. The analysis technique is used multiple regression, which is using STATA version 16. The results show that the size of local government has a significant positive effect on the weakness of internal control. In addition, social assistance funds were also found to have a marginal effect. Locally generated revenue has a significant negative effect on internal control weaknesses. Capital expenditures and follow-up audit results do not have a significant effect on internal control weaknesses. This study is expected to contribute to local governments further improving comprehensive standards in the internal control system with a large scale or size.